Analysis on Social Capital of Community at Subah Village Tayan Hilir in Tourism Development of Lake Lait. (April 2018) - Saputra, L; Muryani, C; Karyanto, P
Abstract: This study aims to determine (1) development of Lake Lait tourism object at Tayan Hilir as a tourism area (2) social capital of community at Subah Village Tayan Hilir in the tourism area development of Lake Lait. The study is a descriptive research, population is the entire head of families at Subah Village, data collection technique used is Cluster Random Sampling with 135 families. Data are collected through direct interviews to the informants. Results of the study show that (1) the Lake Lait tourism object has started to experience a rapid development, for instances in physical, such as Accessibility the widened road to the tourism location, clean water facilities, showers and toilets, numerous restaurants and the number of villas built around the area of Lake Lait; (2) the social capital of the community which could be functioned in the tourism development of Lake Lait area great social network, an openness attitude and a willingness to advance, also a strong tradition and culture.